Calculus and analytic geometry - Mizrahi, Abe; Sullivan, Michael (Belmont, California : Wadsworth Publishing Company, 1986)
In the first edition we set out to write a straight forward, mathematically sound book that would nevertheless capture the interest of students.
1. Introduction -- 2. The limit of a function -- 3. The derivative -- 4. Applications of the derivatives -- 5. The definite integral -- 6. Applications of integral -- 7. Exponential and logarithmic functions -- 8. Trigonometry and hyperbolic functions -- 9. Techniques of integration -- 10. Indeterminate forms; improper integrals; Taylor polynomials -- 11. Infinite series -- 12. Conics -- 13. Polar coordinates; parametric equations -- 14. Vectors; analytic geometry in space -- 15. Vector functions -- 16. Partial derivatives -- 17. Directional derivatives, gradieny, and extrema -- 18. Multiple integrals -- 19. Topics in vector calculus.
Includes index.
Keywords: CALCULATIONS -- PROBLEMS, EXERCISES, ETC